Orthogonal C-arms for Third-Generation Minimally Invasive Correction of Hallux Valgus: A Technique Tip - Daniel D. Bohl MD, MPH; Derek M. Klavas MD; Alaa Mahmoud MD; Eric C. Bellinger MD (Foot & Ankle Orthopaedics)
Graphical Abstract This is a visual representation of the abstract.